Earnings Pressure and Long-Term Corporate Governance: Can Long-Term-Oriented Investors and Managers Reduce the Quarterly Earnings Obsession? - Zhang, Yu; Gimeno, Javier (Organization Science, 2016)
Recent research has shown that managers in publicly traded companies facing earnings pressure—the pressure to meet or beat securities analysts’ earnings forecasts—may make business decisions to improve short-term earnings. Analysts’ forward-looking performance forecasts can serve as powerful motivation for managers, but may also encourage them to undertake short-term actions detrimental to future competitiveness and performance. To identify whether managerial reactions to earnings pressure suggest evidence of intertemporal trade-offs, we explored how companies respond to earnings pressure under different conditions of corporate governance that shape the temporal orientations of managers. Using data on competitive decisions made by U.S. airlines under quarterly earnings pressure, we examined the effect of earnings pressure on competitive behavior under different ownership structures (ownership by long-term dedicated investors versus transient investors) and CEO incentives (unvested incentives that are restricted or unexercisable in the short term, versus vested incentives). The results suggest that companies with more long-term-oriented investors and long-term-aligned CEOs with unvested incentives are less likely to soften competitive behavior in response to earnings pressure, relative to companies with transient investors and CEOs with vested, immediately exercisable stock-based incentives. Using a difference-in-differences (DiD) specification for stronger identification, we also found that firms respond to their rivals’ earnings pressure shocks by increasing capacity and prices, particularly when those rivals do not have long-term-oriented investors and CEO incentives. The evidence is more aligned with the view that the pursuit of short-term earnings as a result of earnings pressure may be detrimental to long-term competitiveness.